Medical Students Expectations, Experiences and Use of E Learning Resources in Higher Education - Qasim Saleem, Muhammad Amin Khan, Syed Ahmed Mahmud, Muhammad Usman, Fatima Aslam, Muhammad Saifullah, Farrukh Sarfraz, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: E-learning, defined here as ‘any learning that uses information and communication technologies is seen as one way to support the advancement of healthcare experts. The adaptability and availability of such modes of delivery are seen globally as advertising opportunities to meet key instruction plans counting lifelong learning and extending participation. Technology-enhanced learning in healthcare education ranges instructive to constructivist approaches. The student constructs new information through investigation of information and reference to involvement and understanding. Objective: To study the expectation and experiences of medical students regarding use of e-learning resources in higher education Study Design: Quantitative cross sectional Settings: Bakhtawar Ameen medical & dental college, Multan Duration: Six months i.e. 1st January 2022 to 30th June 2022 Data Collection Procedure: A pre validated questionnaire was used. Study was carried out at Bakhtawar Ameen medical & dental college, Multan. The total numbers of students were 300 who participated after taking the informed consent. The study was done by simple random sampling technique. All the medical undergraduate students of first to final years must be aged between 20-30 years age. Questionnaire consists of demographic profile, expectation and experiences of medical students regarding use of e-learning resources in higher education Results: The total number of patients who participated in the study was 300 in which 140 (46%) were males and 160 (54%) were females. The undergraduate’s student’s age is in between 20-30 years. On inquiring about student’s expectations and experiences about e learning all the parameters were rated high about e learning which shows the significance of study and p value is <0.1 Practical implication Conclusion: In our study two viewpoints contribute strongly to learning accomplishments and course fulfillment: students’ achievement objectives and the instructor. Students who considered gains in competencies are very special and hence experienced higher achievements. Besides, the results of our study emphasize the instructor’s expertise and part as a counselor and facilitator in learning. Keywords: E-learning, health care, higher education, nursing, student engagement, student experiences, technology-enhanced learning